2017
DOI: 10.3892/or.2017.5904
|View full text |Cite
|
Sign up to set email alerts
|

FTO expression is associated with the occurrence of gastric cancer and prognosis

Abstract: Fat mass and obesity associated (FTO) is a protein-coding gene. FTO gene is an obesity related gene, also known as the obesity gene. It has been reported previously that FTO is associated with a variety of malignant cancers, such as breast, thyroid and endometrial cancer. The aim of the present study was investigate the FTO expression of human gastric cancer and to investigate its clinical value. FTO expression was determined by immunohistochemical analysis with tissue microarrays in GC tissues and correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 21 publications
5
113
0
1
Order By: Relevance
“…24 However, other studies drew a contrasting conclusion and indicated that FTO promotes the proliferation, migration, and invasion of GC cell lines. 16 Numerous studies have indicated that high FTO expression is significantly associated with cancer development. FTO enhances LUSC proliferation and invasion by reducing m6A levels and mRNA stability in myeloid zinc finger 1 (MZF1) mRNA transcription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 However, other studies drew a contrasting conclusion and indicated that FTO promotes the proliferation, migration, and invasion of GC cell lines. 16 Numerous studies have indicated that high FTO expression is significantly associated with cancer development. FTO enhances LUSC proliferation and invasion by reducing m6A levels and mRNA stability in myeloid zinc finger 1 (MZF1) mRNA transcription.…”
Section: Discussionmentioning
confidence: 99%
“…17 The FTO expression level is closely related to low levels of differentiation and lymph node metastasis in GC; FTO overexpression promotes the proliferation, migration, and invasion of GC cell lines. 16 In cervical cancer, upregulated FTO represses the m6A modification of β-catenin and induces chemoradiotherapy resistance. 18 Elevated FTO leads to a low level of m6A modification of the untranslated regions of ankyrin repeat and SOCS box protein 2 and retinoic acid receptor alpha, thus reducing the mRNA and protein levels of these anti-angiogenic genes; C21orf59, MZF1, and taxilin alpha oncogene expression levels then increase, leading to the promotion of acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In melanoma, tumorigenesis is caused by specific demethylation of mRNA of programmmed cell death protein 1, C‐X‐C chemokine receptor 4, and transcription factor SOX‐10. Moreover, for AML, gastric, endometrial, or HNSCC, this protein is involved in cancer development . An elevated FTO level is also responsible for chemotherapy resistance of cervical squamous cell carcinoma (Figure ).…”
Section: N6mea‐demethylases Participate In Cellular Regulatory Processesmentioning
confidence: 99%
“…Another well-studied regulator of RNA methylation is fat mass and obesity-associated protein (FTO), which removes the m6A mark from mRNAs [100]. Increased expression of FTO enhances tumorigenesis of breast cancer as well as acute myeloid leukemia (AML), and is associated with poor prognosis of gastric cancer patients [101][102][103]. Recent efforts have focused on the development of therapies targeting the m6A reader YTHDF2, which selectively inhibits the growth of leukemic stem cells without affecting the proliferation of hematopoietic stem cells in a mouse model of AML [104].…”
Section: Rna Methylation Regulates Epitranscriptomic Plasticitymentioning
confidence: 99%